Prediction of Resistance to Intravenous Immunoglobulin in Children With Kawasaki Disease. (6th January 2017) - Bar-Meir, Maskit; Kalisky, Itai; Schwartz, Andrei; Somekh, Eli; Tasher, Diana
Abstract: Background: Approximately 10%–20% of patients with Kawasaki disease (KD) are refractory to initial intravenous immunoglobulin (IVIg) therapy, and these "nonresponders" are at higher risk of coronary artery abnormalities. Early identification of these patients, who may benefit from additional therapy, is challenging. The aim of the present study is to identify predictors for IVIg resistance. Methods: We reviewed clinical records of 312 consecutive KD patients from 9 medical centers in Israel (development dataset) and 186 patients from additional 5 centers (validation dataset). Using multivariate analysis, we identified predictors of IVIg resistance. A third small prospective cohort of consecutive KD patients from a single medical center was used to test the accuracy of the predictors. Results: Coronary artery abnormalities in the initial echocardiogram and presenting before day 5 of fever were independent predictors of IVIg nonresponse. Using either of these variables generated an area under the receiver-operating-characteristics curve of 0.7 (95% confidence interval [CI], 0.6–0.8). Sensitivity to predict nonresponse was 81% (95% CI, 67–90) and specificity was 50% (95% CI, 44–56). Similar results were found in the validation dataset and in the small prospective cohort. Conclusions: Coronary artery abnormalities in the initial echocardiogram and presenting before day 5 of fever show high sensitivity in identifying IVIg nonresponders among our KD patients.